2002
DOI: 10.1111/j.1572-0241.2002.05683.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of propofol administered by registered nurses with gastroenterologist supervision in 2000 endoscopic cases

Abstract: Propofol can be given safely by appropriately trained nurses under supervision by endoscopists. Technology that allows immediate detection of apnea would likely further improve its safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
74
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(81 citation statements)
references
References 24 publications
0
74
0
7
Order By: Relevance
“…In addition, undesirable cardiovascular or respiratory side effects may occur when propofol is used with opioids. Although previous studies have revealed that propofol is safe when given by registered nurses without any involvement by anesthesia specialists, several patients may require a brief period of mask ventilation for the management of prolonged apnea (10,(18)(19)(20). This side effect occurs because of the narrow therapeutic range and the lack of an antidote in cases of over-sedation and subsequent apnea.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, undesirable cardiovascular or respiratory side effects may occur when propofol is used with opioids. Although previous studies have revealed that propofol is safe when given by registered nurses without any involvement by anesthesia specialists, several patients may require a brief period of mask ventilation for the management of prolonged apnea (10,(18)(19)(20). This side effect occurs because of the narrow therapeutic range and the lack of an antidote in cases of over-sedation and subsequent apnea.…”
Section: Discussionmentioning
confidence: 94%
“…Large published series of patients receiving propofol-based anesthesia for endoscopy have found aspiration to be a rare event. In one, of 2,000 healthy patients undergoing endoscopic procedures with nurse-administered propofol, there were five patients whose oxygen saturation fell to below 85% (19). Several conditions may be associated with increased incidence of pulmonary aspiration during general anesthesia, including extremes of age, male gender, pregnancy, difficult airway management, and factors that decrease gastric emptying, such as concurrent opioid administration, gastrointestinal obstruction or dysfunction, obesity, or depressed level of consciousness (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Although many previous studies examined measurements of hemodynamic changes during endoscopic procedures [14,15,17,27,[31][32][33][34], few have given detailed descriptions of quantitative changes in hemodynamic parameters and oxygen saturation during endoscopic sedation. There are also no reports regarding the frequency of cough during endoscopic procedures performed under sedation.…”
mentioning
confidence: 99%